A Partial Least Squares Path Model of Principals' Performance in School Health Services Based on Spiritual Intelligence in Tabriz Female High Schools - Samereh Moghaddam Hosseini; Behnam Talebi (Shiraz University of Medical Sciences, 2018)
Background: School principals have a crucial role on effectiveness of schools and their performance, especially in school health services programs. The purpose of this study was to predict principals' performance in school health services based on Spiritual intelligence (SI) in high schools of Tabriz (Iran). Methods: The population of this correlational research consisted of all high school principals of Tabriz (520) at the first to fifth educational districts in 2016. According to Krejcie and Morgan's table, and first, stratified random sampling method was used by equally considering the districts of education, and in the second step, random sampling method was used in terms of schools; 225 principals, including 45 principals of each district were selected. Data collection was done by the Spiritual intelligence self-report inventory (SISRI-24, 2009) (α = 0.71) and a researcher-made questionnaire (α = 0.88). Results: The results of correlation test showed that there was a correlation amongst critical existential thinking (r = 0.59, P < 0.001), personal meaning production (r = 0.16, P = 0.013), transcendental awareness (r = 0.26, P < 0.001), conscious state expansion (r = 0.45, P < 0.001) and spiritual intelligence (r = 0.39, P < 0.001) with school principals' performance in school health services. The results of partial least squares regression showed that critical existential thinking (0.62, P < 0.001), transcendental awareness (0.4, P < 0.001), conscious state expansion (0.45, P < 0.001), and spiritual intelligence (0.51, P = 0.003) influenced school principals' performance in school health services. Personal meaning production did not influence school principals' performance in school health services (P = 0.11). Conclusions: Strengthening the spiritual intelligence of school principals could lead to improvement of managerial performance and continuous improvement of education.